Game Genre untuk Permainan Pendidikan Pembelajaran Sejarah Berdasarkan Kebutuhan Pedagogi dan Learning Content - Wenda Novayani (Politeknik Caltex Riau, 2019)
Learning history is learning about several facts in the past, where the learner contains several facts about history. One of the difficulties in learning history is memorized several facts. The memorization learning process can be improved by giving the entertainment experience. Before a game is built, the genre is the most important thing that needs to be defined first. The selection of genre for history learning games is very important because it will determine the effectiveness of the content in conveying the content of the story from the subject matter. It makes students not only know the names of the characters, the dates, and events, but also can convey moral values and patriotism and have critical thinking. In this study, characteristics compatibility is performed from five-game genres, which are a simulation, strategy, action, puzzle and role-playing, and its compatibility with the pedagogy of history learning. As a result, each genre has a different chance, but the RPG genre then followed by a strategy game genre that is found to be very potential and compatible for delivering history learning.